2009
DOI: 10.1080/03124070902748878
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian and Gay People's Concerns about Ageing and Accessing Services

Abstract: There is growing awareness in Australia of the issues faced by lesbian and gay people as they grow older. This paper examines concerns regarding their health-related ageing, growing older in the lesbian, gay, bisexual and transgender (LGBT) community and accessing carers' and aged care services in later life. It is based on a secondary data analysis of a sub-sample of 371 lesbians and gays, drawn from a survey of LGBT ageing conducted by the Queensland Association for Healthy Communities. The original survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 24 publications
2
66
0
3
Order By: Relevance
“…It was reported that this meant that some did not have appropriate people to appoint as substitute decision makers. The extent of older gay men's social connections has been widely debated in the GLBT ageing literature (Hughes 2009;Shippy et al 2004), and there remains mixed findings from research as to the extent to which older gay men may be isolated. Previous researchers have identified that even though they may be more likely to live alone than heterosexual men and lesbians, some older gay men are intimately involved in self-made communities and support networks (Heaphy 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that this meant that some did not have appropriate people to appoint as substitute decision makers. The extent of older gay men's social connections has been widely debated in the GLBT ageing literature (Hughes 2009;Shippy et al 2004), and there remains mixed findings from research as to the extent to which older gay men may be isolated. Previous researchers have identified that even though they may be more likely to live alone than heterosexual men and lesbians, some older gay men are intimately involved in self-made communities and support networks (Heaphy 2007).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The SEEF project has demonstrated the inclusion of a sexual orientation question is feasible and provides data broadly in line with other sexuality-specific investigations. 1 …”
mentioning
confidence: 80%
“…Siinä norminrikkomiseen liittyvän kivun ja trauman aiheuttajaksi tunnistetaan poikkeavuuden sijaan kahlitseva 1 Sukupuoli-ja/tai seksuaalisuunormeja rikkovien suhde usein heteronormatiivisiin terveyspalveluihin on kuitenkin laajemminkin jännitteinen. Monet tutkimukset eri maista kertovat ei-heteroiden potilaiden asiantuntemattomasta tai asiattomasta kohtelusta ja tämän aiheuttamasta pelosta, joka pahimmillaan johtaa siihen, ettei palveluja aina haeta edes todellisen tarpeen tullen (esim, Fredericks, Harbin ja Baker 2017, Hughes 2009, Heaphy ja Yip 2006, Holmqvist ja Rydin 2009Jackson et al 2008, Socada 1998.…”
unclassified